The changing role of management accountants due to technological evolution - Zulkiflee, Nur Qamarina; Wan Mustafa, Wan Muzlaina (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The accounting field has undergone significant transformation in the role of Management Accountants (MAs) due to advancements in technology. This paper explores the evolving responsibilities of MAs amidst automation, digitalization, and artificial intelligence (AI). As organizations increasingly integrate technologies such as AI, blockchain, big data, and cloud computing, traditional accounting tasks like data entry, payroll processing, and report generation are being automated, leading to concerns about job redundancy and the need for workforce retraining. The study highlights the emerging skill gaps in the profession, emphasizing the necessity for MAs to acquire competencies in IT, programming, and data analysis to remain relevant. Additionally, the shift towards real-time financial reporting necessitates the adoption of cloud-based systems and enterprise resource planning (ERP) tools to facilitate prompt decision-making. Ethical and regulatory challenges have also surfaced, including data privacy concerns, cybersecurity risks, and compliance with international financial regulations. Through case examples, such as Baxter’s implementation of JD Edwards (JDE) and Blackline systems, this paper demonstrates the practical implications of these technological advancements on management accounting. The findings suggest that while technology enhances efficiency and accuracy, it also demands a redefinition of the MA’s role, incorporating analytical, technological, and ethical expertise. The paper concludes that organizations must invest in continuous learning and adaptive strategies to ensure that management accountants can navigate the evolving landscape effectively.